MitraClip for the treatment of heart failure with mitral regurgitation: A cost-effectiveness analysis in a Chinese setting - Xia, Wengang; Han, Kangning; Lou, Yake (Frontiers in Cardiovascular Medicine, 2022)
Background Heart failure (HF) with mitral regurgitation is associated with decreased survival. Guideline-directed medical therapy and transcatheter edge-to-edge repair (TEER) are the main options for HF patients with severe mitral regurgitation who are considered high-risk or prohibitive. To date, there have been no studies investigating the cost-effectiveness of MitraClip vs. optimal medical therapy (OMT) in a Chinese setting. Methods A combined decision tree and Markov model were developed to compare the cost-effectiveness MitraClip vs. OMT with a lifetime simulation. The primary outcome was the incremental cost-effectiveness ratio (ICER), which represented incremental costs per quality-adjusted life-year (QALY). The willingness-to-pay (WTP) threshold was set three times of per capita gross domestic product (GDP) in China in 2021, which was 242,928 CNY. MitraClip would be considered cost-effective if the ICER obtained was lower than the WTP threshold. Otherwise, it would be not considered cost-effective. One-way sensitivity and probabilistic sensitivity analyses were performed to validate the robustness of the results. Results After a simulation of the lifetime, the overall cost for a patient in the MitraClip cohort was 423,817 CNY, and the lifetime cost in the OMT was 28,369 CNY. The corresponding effectiveness in both cohorts was 2.32 QALY and 1.80 QALY per person, respectively. The incremental cost and increment effectiveness were 395,448 CNY and 0.52 QALY, respectively, and the ICER was 754,410 CNY/QALY. The ICER obtained was higher than the WTP threshold. Sensitivity analysis validated our finding. Conclusion MitraClip provided effectiveness but with more costs compared with OMT, and the incremental cost-effectiveness ratio obtained was higher than the WTP threshold. MitraClip was considered not cost-effective in Chinese HF patients with secondary mitral regurgitation.